Pengembangan Laboratorium Virtual Matematika pada Materi Bangun Datar Kelas VII MTsS NW Sepit - Wais Al Qorni; Sudi Prayitno; Ratna Yulis Tyaningsih (Griya Journal of Mathematics Education and Application, 2026)
Rapid technological advancements have brought about changes in the world of education, including theirapplication in mathematics instruction. This study aims to develop a virtual mathematics laboratory focusedon plane geometry and to determine its feasibility and practicality. The research design employed is Researchand Development (R&D) using the ADDIE model, which includes the stages of analysis, design, development,implementation, and evaluation. The research subjects consisted of 18 seventh-grade students at MTsS NWSepit. Data collection techniques included interviews, expert validation regarding the media and content, anda student practicality questionnaire. The results showed that the feasibility rating from the media expert was87.33% and from the content expert was 84.28%, with an average of 85.51% in the “highly feasible” category.The students’ practicality level reached 88.75%, falling into the “very good” category. Thus, the developedvirtual laboratory is deemed feasible and practical and has the potential to enhance students’ conceptualunderstanding interactively. Furthermore, the development of this virtual laboratory has a positive impacton the learning process, namely by increasing students’ engagement, interest, and motivation in studyingplane geometry through more engaging and interactive technology-based learning.